2011
DOI: 10.1257/jep.25.2.3
|View full text |Cite
|
Sign up to set email alerts
|

The (Paper)Work of Medicine: Understanding International Medical Costs

Abstract: This paper draws on international evidence on medical spending to examine what the United States can learn about making its healthcare system more efficient. We focus primarily on understanding contemporaneous differences in the level of spending, generally from the 2000s. Medical spending differs across countries either because the price of services differs (for example, a coronary bypass surgery operation may cost more in the United States than in other countries) or because people receive more services in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 33 publications
2
65
0
Order By: Relevance
“…5 Private insurance plans and their public alternatives may differ in the amount of health-improving services (e.g., the quantity of prescription drugs) delivered for a given expenditure level in three ways: 1 the administrative costs incurred in providing the coverage, including costs such as wages and marketing; 2 the prices paid for the actual health services purchased; 3 and profits, which of course apply only to for-profit private insurers. 6 Profits and administration expenses of private health insurance firms have generated substantial debate and policy change in other countries, particularly the United States. 7 For example, after the US Medicare program started allowing members to use private insurers, administrative spending grew substantially.…”
Section: Efficiency and The "Right" Level Of Administrative Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Private insurance plans and their public alternatives may differ in the amount of health-improving services (e.g., the quantity of prescription drugs) delivered for a given expenditure level in three ways: 1 the administrative costs incurred in providing the coverage, including costs such as wages and marketing; 2 the prices paid for the actual health services purchased; 3 and profits, which of course apply only to for-profit private insurers. 6 Profits and administration expenses of private health insurance firms have generated substantial debate and policy change in other countries, particularly the United States. 7 For example, after the US Medicare program started allowing members to use private insurers, administrative spending grew substantially.…”
Section: Efficiency and The "Right" Level Of Administrative Costsmentioning
confidence: 99%
“…7 Similarly, prior estimates have suggested that 39% of the difference in physician and hospital expenditures between Canada and the US results from differences in administrative expenses borne by both insurers and providers. 6 Concern over such spending has led to major policy changes in the US. For example, although the most prominent objective of the Patient Protection and Affordable Care Act of 2010 is to increase health insurance coverage, another provision requires insurers to spend the vast majority of premium revenue on medical care: the proportion of premium income that must be spent on clinical care and quality improvement initiatives is 80% for small-group plans and 85% for large-group plans.…”
Section: Efficiency and The "Right" Level Of Administrative Costsmentioning
confidence: 99%
“…Medical billing is non-trivially complicated, and the resulting administrative costs are well documented (Cutler and Ly 2011). Variation in billing may reflect both differences in the resources devoted to the process and genuine uncertainty over appropriate billing procedures.…”
Section: Implications Of Physician Billing Practicesmentioning
confidence: 99%
“…[1][2][3] A recent survey by Casalino et al found that physicians spend on average 3 h each week interacting with health plans. 4 This time is spent on several administrative tasks, including confirming whether a prescribed medication is covered by a plan's formulary, determining whether a certain specialist is part of a plan's preferred network, and dealing with preauthorization forms.…”
Section: Introductionmentioning
confidence: 99%